2014
DOI: 10.3109/02770903.2014.903965
|View full text |Cite
|
Sign up to set email alerts
|

Effects on asthma and induction of interleukin-8 caused by Asian dust particles collected in western Japan

Abstract: Exposure to an ADS aggravates upper and lower tract respiratory symptoms in patients with adult asthma. ADS airborne particles may increase airway inflammation through enhancement of interleukin-8 transcriptional activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…In a previous study, we showed that airborne particles collected on days of Asian dust storms (ADSs) in western Japan had significantly different effects on induction of secretion of interleukin (IL)-8, compared to the origin soil of the ADS (Watanabe et al, 2014). We proposed that this difference may be caused by substances such as chemicals, metals and microorganisms carried by the ADS, in agreement with the findings of Honda et al (2014).…”
supporting
confidence: 72%
“…In a previous study, we showed that airborne particles collected on days of Asian dust storms (ADSs) in western Japan had significantly different effects on induction of secretion of interleukin (IL)-8, compared to the origin soil of the ADS (Watanabe et al, 2014). We proposed that this difference may be caused by substances such as chemicals, metals and microorganisms carried by the ADS, in agreement with the findings of Honda et al (2014).…”
supporting
confidence: 72%
“…These cells express different receptors such as Toll-like receptors (TLRs), C-type lectin receptors (CTRs), and protease-activated receptors (PARs) that can be triggered by different toxic materials from dust particles. Following receptor-mediated signaling, epithelial cells produce pro-inflammatory cytokines, such as (interleukin(IL)-1β, IL-6, IL-8, IL-12, IL-17A interferon (IFN)-γ, TNF-α) [131][132][133]. Then, elaboration of these cytokines initiates and exacerbates a Th2-type immune response in asthmatic patients [134,135].…”
Section: Pathogeny Of Desert Dust On Respiratory Diseasesmentioning
confidence: 99%
“…Health effects of Asian dust have been a concern recently (Goudie, ; Hashizume et al, ; Zhang et al, ). Results of epidemiological studies have suggested that Asian dust exposure is associated with allergic diseases including asthma and allergic rhinitis (e.g., Chang et al, ; Kanatani et al, ; Watanabe et al., ) and with cardiovascular diseases (e.g., Kamouchi et al, ; Kashima et al, ; Kojima et al, ). In mouse models, inhalation of Asian dust particles caused increased airway inflammation (Ichinose et al, ) and aggravation of allergic rhinitis (Ichinose et al, ).…”
Section: Introductionmentioning
confidence: 99%